Rapid and safe transition to a stand-alone ambulatory surgical center at a major academic medical center. - Aleksander P. Mika; Jacquelyn Pennings; Jacob M. Wilson; Stephen M. Engstrom; Gregory G. Polkowski; J. Ryan Martin (Journal of Orthopaedic Reports)
Introduction: There has been a substantial shift in the number of outpatient total joint arthroplasty performed over the last decade. Furthermore, use of ambulatory surgical centers (ASC) has increased, which has led to improved access to operating rooms and increased efficiency for many arthroplasty surgeons. However, there remains uncertainty as to the safety of this rapid transition from inpatient to outpatient surgery especially at major medical centers usually associated with a more morbid population. Methods: Utilizing the total joint registry at our institution, we identified all total hip and knee arthroplasties from2018–2022 (n = 5000). Surgeries were grouped by timing of surgery, location and by admission status. Patient demographics and clinical outcomes were collected and compared with a focus on readmission and reoperation rates. Results: There was a significant increase in the percentage of same day surgery (SDS) total joint arthroplasty after the transition to an ASC. We identified no significant change in reoperation rate or 30-day readmission amongst SDS patients with our rapid transition to outpatient. Furthermore, the post-transition cohort had a higher incidence of diabetes were more medically complex and the patients were generally older. Conclusion: Within one year of the COVID-19 pandemic onset, we transitioned approximately half of our surgical volume from an inpatient hospital setting to a stand-alone ASC. Furthermore, we did not identify any statistical difference in reoperations, readmissions, or complications even amongst a higher risk population. Therefore, we found a rapid transition to ASC outpatient surgery to be a safe option.